Odious Debt Doctrine: a legal perspective - Abozeid, Hesham Mohamed (AUC Knowledge Fountain, 2014)
International law obliges states to respect their obligations in accordance with the principle of pacta sunt servanda unless the obligation is odious. Citizens of any state should depend on state practice and judicial precedent to repudiate obligation that originated odiously. Jurisprudential and legal controversy arose about the extent of the state’s commitment with debt arising from those obligations. Jurisprudence and the judiciary tried to set a definition of odious debt since the eighteenth century. The difficulty of the definition arises in determining when and how debt is odious, and what are the criteria of odious debt. Another difficulty arises in finding sources of international law to cancel and reject such debt. This paper will be primarily concerned with identifying the precise definition of and normative basis for the doctrine of odious debt in international law. It also concerned with the international legal standards that states can rely on to get rid of that debt. The legal principles are founded on the sources of international law laid down in Article 38 of the Statute of ICJ. Through a review of different sources of international law, the conclusion is that odious debts arise without the consent of the population, without benefit to them, and with the knowledge of the creditor. The paper also concludes that there are at least three legal grounds for repudiating odious debt.